(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The COVID-19 pandemic has changed the world. It changed the way we do business, and it changed our lives in terms of socializing. Nevertheless, it also brought essential changes in the educational segment. This school year, at the tertiary level, courses’ contents and examinations are primarily done online in Slovenia due to the pandemic. In this paper, we examine the perceptions and challenges the third-year students of the Learning and knowledge management course conducted at the School of Economics and Business, University of Ljubljana, are facing. Specifically, we are interested in the challenges the students encountered during the transition to online learning due to the COVID-19 pandemic and the advantages and disadvantages of online learning, as perceived by students. What was used as the method to collect and analyze the data was personal reflection and content analysis. The findings show that students are facing different challenges. Nevertheless, also several advantages and disadvantages related to the online learning process are identified. We conclude by providing practical examples for pedagogical staff to ease the transition for students and avenues for future research.